Collaborative networks in digitalization and society 5.0 : 24th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2023, Valencia, Spain, September 27-29, 2023, proceedings - IFIP WG 5.5 Working Conference on Virtual Enterprises 2023 : Valencia, Spain); Camarinha-Matos, Luis; Boucher, Xavier; Ortiz, Angel; Ohio Library and Information Network (Cham, Switzerland : Springer, 2023)
This book constitutes the refereed proceedings of the 24th IFIP WG 5.5 Working Conference on Virtual Enterprises, PRO-VE 2023, held in Valencia, Spain, in September 2023. The 59 papers presented in this book were carefully reviewed and selected from 119 submissions. They provide a comprehensive overview of the major challenges in sustainability of collaborative ecosystems; risks, security and resilience in networks; collaborative value creation and services; collaborative interactions and human-centered networks; skills and enabling technologies; collaborative healthcare and agile production; and AI, digital twins, and intelligent frameworks
Sustainability of Collaborative Ecosystems -- Influencing Collaboration in Sustainable Business Ecosystems -- The Role of Aggregators and Hubs in Collaborative Prosumer Networks -- Social Sustainability and Resilience in Supply Chains: The Role of Collaboration to Face Risks -- Emerging Technologies Towards Circular and Resilient Networks. -How the COVID-19 Pandemic Has Affected Digital Transformation and Its Relationship to Supply Chain Resilience -- Towards a Flow-oriented Reference Model for Educational Organizations -- The Design of Digital Platform Ecosystem -- Supporting Circular Economy -- Risks and Resilience in Networks -- Collaborative Network Model to Reduce Logistics Costs in a Competition Environment -- The Impact of Industry 4.0 on Supply Chain Resilience Management -- CSC-RMM: A Method for Collaborative Supply Chain Risk Mitigation -- 'If only I knew': Extending the SCSN Vocabulary to Improve the Resilience of Supply Chain Networks -- Resilient and Secure Collaborative Networks -- Collaborative Networks Resilience Approaches: An Enterprise Architecture Perspective -- Roadmap for Resilient Networks Building through Artificial Intelligence -- Securing Collaborative Networks: Requirements of Supporting Secured Collaborative Processes -- Collaborative Value Creation -- Towards Digital Immersive Experiences for Collaborative Value Co-creation in Design -- Simulating the Enhanced Value-Capturing by Using Digitalization in Monetary and Non-Monetary Collaborative Networks -- Supporting the Definition of Key Performance Indicators for Business Models -- Collaborative Value Exploration for Early Product-Service Systems Design: A Group Model Building Approach -- Cyber-Physical Systems in Field- and Customer-Services -- Leveraging Information Visualization through Extended Reality (XR) for Incorporating Changeability in Product-Service Systems -- Extended Reality-Assisted Risk Assessment in Conceptual Product Development -- Economic Assessment of Smart PSS Multi-actor Delivery Networks: Case Study in the Heating Appliance Sector -- Value of Digital in Field Service -- Collaborative Interactions in Human-Digital Contexts -- Using Adversarial Reinforcement Learning to Improve the Resilience of Human-Robot Collaboration in Industrial Assembly -- A Maturity Model for Collaborative Agents in Human-AI Ecosystems -- Integrated Modeling and Collaborative Decision-Making Method Based on Event Logic Knowledge Graph -- Enterprises and Human Integration towards Industry 5.0 -- Emerging Approaches for Enterprises and Human Integration towards Industry 5.0 -- Developing a Collaboration Planning Method for Knowledge Heterogeneity in Construction Supply Chain Management -- A Business Technology Alignment Strategy for Digital Collaborative Networks -- Gamification Operation Design Method for Supply Chain Collaboration -- Learning and Human-centered Networks. -Collaborative Network 5.0: By Design Human Values and Human-Centred based Extended Collaborative Networks -- The Operation Model of the Centre for Learning Technological Entrepreneurship - The CDIT Innovation Hub for Entrepreneurs in Mexico City Case Study -- Dual-Mode: Learning in Higher Education as a Strategy in the Development of Collaborative Networks of the Social and Solidarity Economy for Community Resilience -- Technological Advancements, Future Skills and Collaborative Networks -- Future Learning in a Collaborative "Laboratory" Environment - Requirements to Build up Future Skills -- Factors Affecting the Adoption of AI by Organizations -from the Perspective of Knowledge Workers -- Getting Data Literacy Education Ready for the Future -- Enabling Technologies for Healthcare 5.0 -- Digital Applications in Pulmonary Rehabilitation: Preliminary Evaluation of a Hybrid Program for the Continuity of Care -- ActivE3: Fostering Social Inclusion through Collaborative Physical and Cognitive Exercise -- Linguistic Indicators of Depressive Symptoms in Conversations with Virtual Humans -- Start-up Innovation and Growth in Health-related Industries -- Collaborative Networks in Personalized Healthcare -- Towards a Digital Collaborative Framework for an Efficient Medication Errors Management -- Analysis of a Collaborative Resilient Solution based on Real-time Re-optimization for Home Health Care Routes Subject to Disruptions by Discrete Event Simulation -- Capacity Planning for Ambulatory Surgeries in Collaborative Network of Hospitals -- Agile Production Networks in the Digitalization Era. -Collaborative Network for the Development of Non-Destructive Inspection Technologies: Elicitation Requirements in an Industrial Environment -- Digital Platforms and Enterprise Agility: A Systematic Literature Review -- Towards an Analysis of the Adaptability Potential of a Collaborative Manufacturing System -- Collaboration in the AECO Sector Supported by Digital Twins -- AI-supported Commissioning of Buildings: Verification of Collaboration Achievements as Pre-requisite for Intelligent Building Operations.-Improving Safety on Construction Sites by Exploiting IoT, Digital Twins, and Data Fusion -- Computer Vision for Construction Progress Monitoring: A Real-Time Object Detection Approach -- Digital Twins as Enabler for Long Term Data Management Using Building Logbooks -- Artificial Intelligence and Collaborative Environments -- AI-powered Chatbots and the Transformation of Work: Findings from a Case Study in Software Development and Software Engineering -- Artificial Intelligence to Support Collaboration in the Industrial Equipment Life Cycle -- Brain-Computer-Interface (BCI) based Smart Home Control using EEG Mental Commands -- Time and Networks: Reflections and Good Practices for the AI-based Digital Era -- Intelligent Frameworks -- Making Sense of Digital Twins: An Analytical Framework -- RPA Experiments in SMEs through a Collaborative Network -- Can Artificial Intelligence-enabled Service Interactions Improve the Perception of Service Quality -- Collaborative Interactions and Processes -- A Lifecycle Protection Framework for Creative Artifacts: Blockchain-enabled Collaborative Evidence Network, Evaluation and Audit -- Exploring Stakeholders' Perceptions of Interactions in Competitive Sports: A Study on the Introduction of AI in the Process -- A Synergistic Approach Towards Agile and Resilient Command and Control and Collaborative Networks -- Understanding the Relationship between Business Model and Business Process Elements
Includes author index
Keywords: Business enterprises -- Computer networks -- Congresses; Conference papers and proceedings